Discursive Battle Over Belis: Online Debates on Bridewealth Tradition in Nusa Tenggara Timur - Gesiradja, Asriyanti Saputri; Habsari, Sri Kusumo; Rais, Wakit Abdullah (Humaniora, 2025)
This study examines the discursive transformations and contested meanings of belis, a dowry tradition in East Nusa Tenggara, by analyzing how it is debated, redefined, and reinforced in digital spaces. Using Foucauldian Discourse Analysis, it interrogates the power relations, regimes of truth, and subject positions articulated in public discourse surrounding belis. Traditionally, belis served as a social contract symbolizing the union of two families through marriage and reinforcing communal bonds through the exchange of valuable items from the groom’s family to the bride’s. However, contemporary interpretations of belis have shifted under social, economic, and cultural transformations.. Drawing on data from YouTube broadcasts and user-generated comments, this research explores how digital platforms mediate public discourse on belis. The analysis reveals that online debates increasingly frame belis through the lens of economic logic and social prestige, often prioritizing material value over its metaphysical and symbolic significance. This discursive shift reflects a broader cultural reconfiguration in which traditional practices are questioned, redefined, or reinforced within digital spaces. Ultimately, the study argues that the transformation of belis illustrates how digital discourse contributes to the rearticulation of cultural meaning, exposing tensions between heritage and modernity, and between symbolic reciprocity and commodification.